Complete denture impression techniques: Evidence-based or philosophical - Singla Shefali (Wolters Kluwer Medknow Publications, 2007)
Code of practice is dangerous and ever-changing in today′s world. Relating this to complete denture impression technique, we have been provided with a set of philosophies - "no pressure, minimal pressure, definite pressure and selective pressure". The objectives and principles of impression-making have been clearly defined. Do you think any philosophy can satisfy any operator to work on these principles and achieve these objectives? These philosophies take into consideration only the tissue part and not the complete basal seat, which comprises the periphery, the tissues and the bone structure. Under such circumstances, should we consider a code of practice dangerous or should we develop an evidence-based approach having a scientific background following certain principles, providing the flexibility to adapt to clinical procedures and to normal biological variations in patients rather than the rigidity imposed by strict laws?